THE RESISTANCE OF THE MAIN CHARACTER AGAINST RACISM IN THE NOVEL THE HATE U GIVE BY ANGIE THOMAS - Ima Sustika Dewi; Ni Made Widisanti S; Ade S Natawiria (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
This thesis deals with racism in the novel ‘The Hate U Give written by Angie Thomas. It aims at analyzing racism due to inherent stereotypes that still exist now. The descriptive analysis method is applied in this research to go with intrinsic and extrinsic approaches. The writer studies character, conflict, setting, and irony as the intrinsic elements in order to deeply analyze the topic of discussion. As for extrinsic theory, this thesis analyzes racism and how to deal with it, including the forms and effects of racial injustice. In the novel, the main character witnesses her friend killed by the white police officer. She struggles to win justice in fighting racism. The result of this research is that modern racialism, anti-black issues as well as discrimination that still applies now.Keywords: racism; resistance; justice.